Optimisation of Production Condition of Alkaline Protease Using Indigenous Bacillus subtilis from Agricultural Soil: Bacillus subtilis for Protease Production - Solangi, Barkat Ali; Nawaz, Hafiz Rub; Nadeem, Uzma; Zehra, Beena; Noor, Agha Asad (Biological Sciences - PJSIR, 2018)